INSIDER RESEARCHERS: CHALLENGES & OPPORTUNITIES - Khaliza Saidin (Proceedings of The ICECRS, 2016)
A researcher plays an important role in the success of the topic being researched. Being an insider researcher could help the researcher to have more understanding about their research and the phenomena being studied. However, previous research revealed inconsistent results. Some argue that becoming an insider researcher could lead to a loss of objectivity and bias, while others found that it has potential to balance the ways issues being researched. The objective of this qualitative case study is to explore the potential and challenges of being an insider researcher. Ten excellent teachers were selected using purposive sampling and they were interviewed face to face. The findings revealed some advantages to the insider researcher in understanding the issues being studied as she has the common knowledge of the life, problems and challenges they face as excellent teachers. Moreover, the researcher also managed to reduced “red tape” in getting contact with the participants. The findings from this study enriched the literature on being an insider in educational research from the perspectives of excellent teachers.